EXPLORING ACADEMICS’ UNDERSTANDING ON THE TRANSFORMATION OF UNIVERSITY COLLEGE TO UNIVERSITY - Sara Asmawati Shariffuddin; Jamal Rizal Razali (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Transformation of university college to full-university status is one of many efforts by Ministry of Education to transform the quality of tertiary education in Malaysia. In transforming this type of higher education institution, it is imperative to not overlook at the significance of academics’ understanding towards the transformation process in order to obtain their commitment and elevate their motivation in implementing the strategies to achieve the transformational goal. Therefore, this study explores the academics’ understanding pertaining to the transformation of university college to university and the recommendations on enhancing understanding. A qualitative approach was utilized to gauge on the academics’ understanding whereby twelve academics were interviewed for data collection. Nine elements of the academics’ understanding were identified. Then, recommendations on improving academics’ understanding were proposed.